ATPase Inhibitory Factor 1 Is Critical for Regulating Sevoflurane-Induced Microglial Inflammatory Responses and Caspase-3 Activation - Xu, Yaru; Gao, Ge; Sun, Xiaoru; Liu, Qidong; Li, Cheng (Frontiers in Cellular Neuroscience, 2021)
Postoperative delirium (POD) is one of the most important complications after surgery with general anesthesia, for which the neurotoxicity of general anesthetics is a high-risk factor. However, the mechanism remains largely unknown, which also hinders the effective treatment of POD. Here, we confirmed that a clinical concentration of the general anesthetic sevoflurane increased the expression of inflammatory factors and activated the caspase-3 by upregulating ATPIF1 expression in microglia. Upregulation of ATPIF1 decreased the synthesis of ATP which is an important signaling molecule secreted by microglia. Extracellular supplementation with ATP attenuated the microglial inflammatory response and caspase-3 activation caused by sevoflurane or overexpression of ATPIF1. Additionally, the microglial inflammatory response further upregulated ATPIF1 expression, resulting in a positive feedback loop. Animal experiments further indicated that intraperitoneal injection of ATP significantly alleviated sevoflurane anesthesia-induced POD-related anxiety behavior and memory damage in mice. This study reveals that ATPIF1, an important protein regulating ATP synthesis, mediates sevoflurane-induced neurotoxicity in microglia. ATP supplementation may be a potential clinical treatment to alleviate sevoflurane-induced POD.